Borderland generation : Soviet and Polish Jews under Hitler - Koerber, Jeffrey (2020)
"Borderland Generation: Soviet and Polish Jews under Hitler" explores the Holocaust in eastern Poland and the western Soviet Union under German occupation during World War II. Drawing upon written and oral sources recorded in the multiple languages of the region, many never before examined by scholars, the book follows the trajectories of individuals too often portrayed in the historical literature as faceless victims.